Konsumsi Media Dan Identitas Budaya Di Kalangan Remaja Juwana, Kabupaten Pati - Tsania Mishbahun Naila; Primi Rohimi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Artikel ini mengeksplorasi hubungan antara konsumsi media dan identitas budaya di kalangan remaja Juwana, Kabupaten Pati, dengan fokus pada pengaruh media terhadap pemahaman dan keterikatan remaja terhadap budaya lokal. Penelitian ini didorong oleh tren peningkatan penggunaan media sosial yang berpotensi mengubah cara remaja memahami nilai-nilai budaya daerah. Konsumsi media yang tidak terkontrol dapat memudarkan nilai-nilai lokal, sementara pemanfaatan yang tepat dapat memperkuat identitas budaya. Kebaruan penelitian terletak pada pendekatan kualitatif yang memadukan wawancara mendalam dan observasi partisipatif untuk menggali pengalaman remaja dalam menggunakan media. Data diperoleh melalui wawancara terstruktur dengan remaja dan pengamatan terhadap pola interaksi mereka dengan media. Hasil penelitian menunjukkan bahwa meskipun media sosial mendorong kesadaran akan tradisi dan nilai budaya lokal, penggunaan bahasa gaul yang dominan menciptakan kesenjangan generasi yang dapat melemahkan keterikatan budaya. Penelitian ini menggarisbawahi pentingnya sinergi antara keluarga, sekolah, dan komunitas dalam membangun literasi media yang bijak. Dengan literasi media yang baik, konsumsi media dapat dimanfaatkan sebagai sarana untuk memperkuat identitas budaya remaja tanpa mengabaikan nilai-nilai lokal. Oleh karena itu, peran edukasi dalam mengarahkan pemanfaatan media menjadi sangat krusial demi pelestarian budaya lokal di era digital. This article explores the relationship between media consumption and cultural identity among the youth of Juwana, Pati Regency, with a focus on the influence of media on adolescents' understanding of and attachment to local culture. This research is motivated by the increasing trend of social media use that has the potential to change the way adolescents understand local cultural values. Uncontrolled media consumption can diminish local values, while proper utilization can strengthen cultural identity. The novelty of the research lies in the qualitative approach that combines in-depth interviews and participatory observation to explore adolescents' experiences in using media. Data was obtained through structured interviews with teenagers and observations of their interaction patterns with the media. The results show that although social media encourages awareness of local cultural traditions and values, the dominant use of slang creates a generation gap that can weaken cultural attachment. This research underscores the importance of synergy between families, schools and communities in building wise media literacy. With good media literacy, media consumption can be utilized as a means to strengthen adolescents' cultural identity without ignoring local values. Therefore, the role of education in directing media utilization is crucial for the preservation of local culture in the digital era. This research explores the relationship between media consumption and cultural identity among teenagers in Juwana, Pati Regency, with a focus on the main question regarding how media influences teenagers' understanding and attachment to local culture. The background to this problem arises from the increasing use of social media which has the potential to change the way teenagers understand regional cultural values. The novelty of this research lies in the qualitative approach which combines in-depth interviews and observations to explore teenagers' experiences in media consumption. The methodology used involves analysis of data from interviews with teenagers and observations of their interactions with the media. The main results show that teenagers who are active on social media tend to be more aware of local cultural traditions and values, although the use of slang creates a generation gap that can reduce attachment to that culture. This research emphasizes the importance of collaboration between families, schools and communities in educating teenagers so they can use media wisely. The conclusion of this discussion confirms that with the right approach, media consumption can strengthen cultural identity without ignoring local values, so it is important to increase media literacy among teenagers.